Exosome-Mediated miR-155 Transfer from Smooth Muscle Cells to Endothelial Cells Induces Endothelial Injury and Promotes Atherosclerosis - Zheng, Bin; Yin, Wei-Na; Suzuki, Toru; Zhang, Xin-Hua; Zhang, Yu; Song, Li-Li; Jin, Li-Shuang; Zhan, Hong; Zhang, Hong; Li, Jin-Shui; Wen, Jin-Kun (Molecular therapy, 2017)
The vascular response to pro-atherosclerotic factors is a multifactorial process involving endothelial cells (ECs), macrophages (MACs), and smooth muscle cells (SMCs), although the mechanism by which these cell types communicate with each other in response to environmental cues is yet to be understood. Here, we show that miR-155, which is significantly expressed and secreted in Krüppel-like factor 5 (KLF5)-overexpressing vascular smooth muscle cells (VSMCs), is a potent regulator of endothelium barrier function through regulating endothelial targeting tight junction protein expression. VSMCs-derived exosomes mediate the transfer of KLF5-induced miR-155 from SMCs to ECs, which, in turn, destroys tight junctions and the integrity of endothelial barriers, leading to an increased endothelial permeability and enhanced atherosclerotic progression. Moreover, overexpression of miR-155 in ECs inhibits endothelial cell proliferation/migration and re-endothelialization in vitro and in vivo and thus increases vascular endothelial permeability. Blockage of the exosome-mediated transfer of miR-155 between these two cells may serve as a therapeutic target for atherosclerosis.